Provision of Menstrual Disorder Education Through Whatsapp Group in Kruwed, Sempor, Kebumen - Lutfia Uli Na’mah; Umi Laelatul Qomar; Eka Novyriana (Urecol Journal. Part F: Community Development, 2022)
Menstruation or menstruation is periodic and cyclic uterine bleeding, accompanied by the shedding of the endometrium. Menstrual disorders or menstruation are abnormalities that occur in the menstrual cycle. Some menstrual disorders that often occur include menstrual pain, irregular menstrual cycles, excessive bleeding and others. The results showed that 50% of women in the world experience disturbances in the menstrual process. In Indonesia, the number of menstrual disorders reaches 55% and 64,25% experience dysmenorrhea. Several disorders that occur during menstruation can affect women's health. Therefore, it is important for women, including men, to understand various menstrual disorders as a precaution against unwanted health conditions. However, people sometimes do not understand about the menstrual disorder. Providing education during a pandemic like today can be done using information technology available to the public. In this community service program, education is carried out using the WhatsApp application which is owned by many residents. Before and after giving education, a questionnaire was given to measure the level of knowledge about menstrual disorders. The result before giving education was 23,5 %, and after giving education it was 70,59% good. So it can be concluded that there is an increase in knowledge of 48,9 %.